Pengembangan Media Pembelajaran Menggunakan Software Prezi pada Materi Atom, Molekul dan Ion Kelas VIII untuk SMP Tahun 2018 - mega sukmawati (Wacana Didaktika, 2019)
This research is motivated student difficulties in understanding the material Atoms, Molecules and Ions. This development research aims to develop learning media material Prezi on Atomic, Molecular and Ion class VIII as a viable learning medium. Feasibility study media developed Prezi is seen based on the validity, practicality and effectiveness. This development research using ADDIE development model that includes phases: Analyze, Design, Development, Implement and Evaluate. The results showed that the development of instructional media Prezi on material Atoms, molecules and ions get an average score of 3.76 with very valid category. implementation of instructional media use Prezi achieved a score of 92.94% and a positive response as much as 97.13% categorized as very practical. Results posttest students demonstrate mastery of students reached 86.21 and mastery learning indicator reached 85.42 categorized as very effective. Based on these results it can be concluded that the instructional media material Prezi on Atomic, Molecular and Ion fit for use as a medium of learning.